MENGKAJI PEMIKIRAN TASAWUF KIAI AHMAD RIFA`I KALISALAK DALAM KITAB TARAJUMAH - Abdul Basit Atamimi; Aip Syarifudin (An-Nufus, 2020)
Kiai Rifa'i is one of the leading Islamic reformers on the island of Java, precisely in Kalisalak Village, Batang Regency, around the 19th century. He is a cleric figure who is worried about the condition of the Muslim community, especially rural communities who still lack religious knowledge. He tried to teach with the method of da’wah (Islamic preaching) that was easily accepted by the public at that time, namely the method of Islamic preaching - which might be a new one - by translating Islamic religious books in Javanese. One of them is the Tarajumah book which contains Sufism teachings. The purpose of this article is to find out how Kiai Rifa`i's Sufism thought in the Tarajumah book. Apart from its content, this book is interesting because it is able to instill the anti-Dutch colonial ideology as one of Kiai Rifa'i's criticisms of the Dutch colonialism and the traditional ulama (Islamic clerics) who were his collaborators. The research approach uses library research, namely research that uses literature. In obtaining data, the authors used written materials, such as books by Kiai Rifa'I, as primary data sources; as well as books, journals, manuscripts, and other documents related to the object of research as secondary references which are indeed related to the history, teachings and thoughts of Kiai Ahmad Rifa`i about Sufism and the Rifa`iyah congregation. This research found three main findings: first, the Dutch colonial government was kafir and haram to follow because it oppressed the people; second, the traditional bureaucrats, including the rulers and ulama who collaborated with the Dutch; third, K.H Ahmad Rifa`i taught eight praiseworthy qualities, and eight despicable qualities.